Projeção dos impactos econômicos da redução na alíquota do ICMS na economia do estado do Amazonas : uma abordagem de equilíbrio geral computável (MINIMAN) - Silva, Sergio Marinho da (2014)
The aim of this study was to analyze the impact of the reduction of the ICMS practiced in Amazonas state tax, contextualizing with controversy about tax war between the states. using data from the Amazonian economy in 2006 through the input-output matrix, using the methodology for the treatment of computable general equilibrium data and analyze the results, contributing to the fostering of this matter of great importance to the industry located in the western Amazon, mainly in the city of Manaus through the economic development of the Free Zone of Manaus model (ZFM).